131k views
0 votes
G(x)= -1/2x+5

A) use the definition of a one-to-one function, to show that G(x) defines a one-to-one function.

B) find the inverse of g(x)

User Cumhur Ata
by
5.2k points

1 Answer

5 votes

Answer:

Given
g(x)=(-1)/(2)x+5 we can conclude the following things:

A)
g is one-to-one.

B)
g's inverse is given by
g^(-1)(x)=-2(x-5).

Explanation:

A) If it is one-to-one, then f(a)=f(b) implies only a=b.

The function is
g(x)=(-1)/(2)x+5.

Let's see what
g(a)=g(b) implies here.


g(a)=g(b)


(-1)/(2)a+5=(-1)/(2)b+5

Subtract 5 on both sides:


(-1)/(2)a=(-1)/(2)b

Multiply both sides by -2:


a=b

This is exactly what we need to show that
g is one-to-one.

---------------------------------------------------------------------------------------------

If you look at a visual of
g on a graph. You would see it passes the horizontal line test making it one-to-one. (It is is just a diagonal line after all.)

B)


g(x)=(-1)/(2)x+5


y=(-1)/(2)x+5

The inverse is the swapping of
x and
y and then we want to remake the new
y the subject of the equation.

That is we have to solve the following for
y:


x=(-1)/(2)y+5

Subtract 5 on both sides:


x-5=(-1)/(2)y

Multiply both sides by -2:


-2(x-5)=y


y=-2(x-5)

So
g^(-1)(x)=-2(x-5).

--------------------------------------------------------------------------------------------

Let's verify.

So we should get that
g^(-1)(g(x))=x \text{ and } g^(-1)(g(x))=x.

Let's see what happens:


g^(-1)(g(x))


g^(-1)((-1)/(2)x+5)


-2((-1)/(2)x+5-5)


-2((-1)/(2)x+0)


-2((-1)/(2)x)


1x


x -So that looks good so far.


g(g^(-1)(x))


g(-2(x-5))


(-1)/(2)(-2(x-5))+5


(x-5)+5


x-5+5


x+0


x -So that looks good.

Both ways check out so we indeed found the inverse of
g.

User Slecorne
by
6.2k points